A Concise Discrete Adaptive Filter for Frequency Estimation Under Distorted Three-Phase Voltage - Quan, Xiangjun; Dou, Xiaobo; Wu, Zaijun; Hu, Minqiang; Chen, Feng (IEEE transactions on power electronics, 2017)
To improve the control performance for grid-tied power converters, the fundamental frequency and harmonics of the grid voltage should be quickly and accurately estimated even under distorted voltage condition. This paper introduces a straightforward discrete adaptive filter to observe fundamental and harmonic sequence components of the grid voltage. The proposed filter possesses a simple and straightforward implementation. Based on the newly developed filter, frequency error transmission was analyzed when the frequency of the input voltage was unequal to the center frequency of the filter. Consequently, a frequency estimation loop was designed to adapt to the frequency variation for the filter. Compared to previous algorithms, the proposed algorithm has a better dynamic performance rating for frequency estimation, robust stability, and a simpler implementation. The effectiveness of the algorithm is verified by simulations and laboratory experiments.